Size effect and merger dominance in salesforce integration - Oh, Joon-Hee (The Journal of business & industrial marketing, 2021)
Purpose This study aims to test the authors’ theory that in an integrated sales team, the larger team (either from the acquiring or acquired firm) dominates the smaller team, even though it may be less competent than the smaller one, and that the level of competence of the integrated entity with the dominant but inferior larger team is bound to deteriorate. Design/methodology/approach The study tests the theory by conducting a laboratory experiment. Findings The results from the experiment show that an asymmetrical employee composition structure creates merger dominance in the post-integration group and influences the integration performance. Research limitations/implications Considering the lack of mergers and acquisitions research in the marketing literature, the author believes that this study contributes new information to the literature. The finding that an integrated entity with a dominant but inferior larger partner will demonstrate a resulting degeneration of competence invites empirical research for validation. Practical implications The integration of sales teams is central to ensuring revenue growth and driving the value that mergers promise but often fail to realize. The study findings provide some practical insights in this regard. Originality/value Mergers between asymmetrical partners are common phenomena. However, few studies have investigated how an unequal size of sales teams in pre-merger firms influences the effective integration of different sales teams. To fill this research gap, this study examines whether the involvement of an unequal number of salespeople from pre-merger firms in a post-merger sales team may influence its post-merger performance.